Antepartum high-frequency fetal heart rate sinusoidal rhythm: computerized detection and fetal anemia - Reddy, A; Moulden, M; Redman, C (2009)
Objective: Our aim was to identify antepartum fetal heart rate (FHR) records of high-frequency (HF) sinusoidal rhythms from an electronic database (1983-2003) and determine clinical outcomes. Study Design: At the John Radcliffe Hospital (Oxford, UK), 72,297 traces from 19,506 women were analyzed using an algorithm that identifies HF sinusoidal rhythms. The case records were reviewed. Results: There were 15 (0.21/1000) traces from 8 (0.41/1000) women with an HF sinusoidal rhythm. In 5 of 8 women (62.5%), this pattern was associated with fetal anemia (hemoglobin < 10.0 g/dL). Their FHR patterns were distinguished from those of the other nonanemic fetuses by significantly lower long-term variability. Conclusion: An antepartum HF sinusoidal rhythm is rare but associated with fetal anemia, particularly if it is combined with reduced long-term variability without episodes of high FHR variability within 60 minutes. The automated system can alert inexperienced staff, who supervise FHR monitoring, by an online warning. © 2009 Mosby, Inc. All rights reserved.